ChemInform Abstract: A Convenient Synthesis of Dialkyl 2‐(2‐Haloethylidene)malonates, Cyanoacetates and Halocrotonates by One Carbon Extension. Issue 40 (October 2015) - Sathishkumar, S.; Mahasampathgowri, S.; Balasubramanian, K. K.; Saiganesh, R.
Abstract using dimethylsulfoxonium methylide